The Intention for Providing Exclusive Breastfeeding Associated from Self-Leadership and Psychological Capital of Mother - Fauziyatun Nisa; Nyoman Anita Damayanti; Fendy Suhariadi; Fritria Dwi Anggraini; Siska Nurul Abidah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Intention is a crucial for influencing a mother’s decision to breastfeeding. With the high breastfeeding intentions, mothers can help achieve the government program, namely exclusive breastfeeding for 6 months, with seeing the importance of influencing mother’s behavior in breastfeeding, it is necessary to study the mother’s intention to provide exclusive breastfeeding. This research was conducted in the city of Surabaya with the researcher’s consideration, there are still many mothers who do not provide exclusively breastfeeding, so the achievement of exclusive breastfeeding in the city of Surabaya still not fulfill the target. The purpose of this research is to examine the intention to provide exclusive breastfeeding in terms of selfleadership and psychological capital of mothers in the city of Surabaya. This research used a quantities approach with observational research and was classified as a cross sectional. The sample of this research were pregnant women of 108 respondents. The independent variables of this research were education, attitude, age, occupation, parity, knowledge, breastfeeding self-efficacy, self-leadership, psychological capital, and family support. Whereas, the dependent variable is the mother’s intention to provide exclusive breastfeeding. The research was obtained through a questionnaire. This research used a logistic regression test with the purpose to identify the factors that influencing between the independent variable on the dependent variable. The results showed that the factors that influenced the intention to provide exclusive breastfeeding were psychological capital (Sig: 0.000, B = 4.255), self-leadership (sig = 0.015, B = 3.482), breastfeeding selfefficacy (sig = 0.004, B = 5.627) and family support (sig = 0.041, B = 2.142). The conclusion is mother’s ability to lead herself, has an important role in the paradigm and psychological capital of mother’s in their behavior, one of the intentions to provide exclusive breastfeeding behavior. Consequently, it is imperative for mother to have strong self-leadership as well as a mother’s psychological capital in intending to do something and realizing that intention in a real action.